Consumers in a globalised world effectiveness of consumer protection institutions - Misra, Suresh; Dhaka, Rajvir S. (2006)
Consumer protection entails protecting the rights and interests of the consumers in matters of availability, quality, quantity and price of goods and services. It infact promotes the concept of value for money and enhances the trust between the customer and the producer or provider. Consumer protection policy recognises that consumers often face imbalances in economic terms, educational levels and bargaining power and that the consumers should have the right of access to non-hazardous products as well as the right to promote just, equitable and sustainable economic and social development. - Reproduced.
Keywords: Consumer protection